PENERAPAN PEMBELAJARAN BERDIFERENSIASI TERHADAP KEMAMPUAN BERPIKIR KREATIF DAN KEMANDIRIAN BELAJAR MATEMATIS MURID SEKOLAH DASAR - Deswita, Deswita; Hasnawati, Hasnawati; Yumiati, Yumiati (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The aim of this research is to find out whether there is a difference in increasing the creative thinking abilities and learning independence of control and experimental class students in class IV of SD N 32 Tanjuang Bonai. This type of research is experimental research. The population in this study were all fourth grade students at SD N 32 Tanjuang Bonai which consisted of two classes. The samples in this research were class IV A and class IV B. The instruments used in this research were test sheets and questionnaires. Hypothesis testing is carried out using the t-test. Based on the results of data analysis, there is a significant difference between the thinking abilities of students in the experimental class and the control class which applies differentiated learning. The average N-Gain gain score for the experimental class was 0.72 and the control class was 0.46. Meanwhile, regarding the relationship between differentiated learning and student learning independence, the t-count in the t-table is 0.758 < 2.069, so rejecting Ha and accepting H0, it can be concluded that differentiated learning has no effect on student learning independence.